Increased erosion in biochar-amended soil: importance of integrating erosion control blankets and vegetation - Hossain, Monir; Jotisankasa, Apiniti; Aramrak, Surachet; Kamchoom, Viroon; Nishimura, Satoshi; Nontananandh, Supakij; Muanlhao, Tananop; Semmad, Surat (My University, 2026)
Although biochar is widely recognized for enhancing various soil properties, its impact on soil erosion resistance remains unclear and sometimes shows contradictory results. The main objective of this study is to quantify the effects of corn-cob biochar amendment, both with and without erosion control blankets (ECB), as well as the influence of biochar/compost incubation time on erosion resistance of a silty sand. The study also investigates the effects of biochar on Atterberg limits, shear strength, and thermal conductivity. As biochar content increases from 0 % to 20 %, the liquid limit (LL), plastic limit (PL), and shrinkage limit (SL) rise by 8 %–10 %, suggesting that biochar-amended soil (BAS) retains more water without losing strength. The addition of biochar has minimal impact on the shear strength of BAS at lower normal stresses (<45 kPa) but reduces its thermal conductivity by about 70 %. Submerged jet erosion tests show that biochar alone increases soil erosion in BAS. However, when combined with ECB and vegetation, erosion is significantly reduced (up to 39 %). Overall, this study underscores the importance of utilizing biochar in combination with ECB and such vegetation as ruzi grass to mitigate soil erosion in the silty sand.
Keywords: Biochar; Erosion; Erosion control blanket; Submerged jet erosion test; Thermal conductivity; Tropical soil